2006
DOI: 10.1128/jvi.00585-06
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis Reveals a Correlation between the Expansion of Very Virulent Infectious Bursal Disease Virus and Reassortment of Its Genome Segment B

Abstract: Infectious bursal disease virus (IBDV) is a birnavirus causing immunosuppressive disease in chickens.Emergence of the very virulent form of IBDV (vvIBDV) in the late 1980s dramatically changed the epidemiology of the disease. In this study, we investigated the phylogenetic origins of its genome segments and estimated the time of emergence of their most recent common ancestors. Moreover, with recently developed coalescence techniques, we reconstructed the past population dynamics of vvIBDV and timed the onset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 43 publications
(47 reference statements)
9
66
0
2
Order By: Relevance
“…The current study demonstrates that both genomic segments of 94432, both of which are phylogenetically related to those of vvIBDVs, do contribute to pathogenicity. This primary contribution of VP1 to the pathogenicity of vvIBDV is consistent with the findings of a chronophylogenetic study suggesting that vvIBDV expansion was almost concomitant with the emergence of the typical vvIBDV-like segment B (38).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The current study demonstrates that both genomic segments of 94432, both of which are phylogenetically related to those of vvIBDVs, do contribute to pathogenicity. This primary contribution of VP1 to the pathogenicity of vvIBDV is consistent with the findings of a chronophylogenetic study suggesting that vvIBDV expansion was almost concomitant with the emergence of the typical vvIBDV-like segment B (38).…”
Section: Discussionsupporting
confidence: 76%
“…VP2 is, however, unlikely to be the only factor for virulence: laboratory-engineered reassortant viruses derived from vvIBDV exhibited delayed replication in the bursa (37) or failed to induce morbidity and mortality (31) unless they also had a typical vvIBDV-related segment B. This observation is consistent with the phylogeny-based hypothesis that both genome segments may be involved in the emergence of vvIBDV (38,39). Recently, this hypothesis was substantiated by the isolation of three naturally occurring segment B-reassorted vvIBDV isolates, all with reduced pathogenicity in chickens (40,41).…”
Section: Nfectious Bursal Disease Virus (Ibdv) Of Chickens (Gallus supporting
confidence: 79%
“…The genome of IBDV is a bisegmented doublestranded RNA consisting of 2 segments (A and B); segment A encodes VP5 and polyprotein (VP2-VP4-VP3), while segment B encodes VP1 protein (5). The coinfection with very virulent IBDV (vvIBDV) and attenuated IBDV strains led to exchange of the double-stranded genomic RNA segments to generate new reassortant viruses (2,3,11).…”
Section: Nfectious Bursal Disease Virus (Ibdv) Belongs To the Familymentioning
confidence: 99%
“…Genetic analyses revealed that these IBDV strains have nucleotide and amino acid signatures and constitute well-supported independent clades in phylogenetic trees (Boot et al, 2000;van den Berg, 2000;Le Nouën et al, 2005;Hon et al, 2006). Besides the three lineages corresponding to c, va and vv strains, phylogenetic trees also resolve an independent lineage for the ca strains that comprise vaccine strains maintained in the laboratory and vaccine-like virus collected from the field (Kim et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…By studying both segments, it is possible to analyse their coevolution, to detect the occurrence of natural reassortants and to determine the role of VP1 in pathogenicity (Le Nouën et al, 2006;Escaffre et al, 2013). VP1 phylogeny resolves a lineage corresponding to the vvIBDV strain and a nonvvIBDV clade constituted by the remaining strains and serotype 2 viruses (Hon et al, 2006).…”
Section: Introductionmentioning
confidence: 99%